Determination of the first ionization energy of polonium by resonance ionization spectroscopy: Part II: measurement of odd-parity Rydberg states at CERN-ISOLDE - Fink, Daniel (Spectrochimica acta. Part B, Atomic spectroscopy, 2019)
Polonium (Po) is one of the rarest elements in Earth's crust. None of its isotopes are stable and sufficient amounts for systematic experimental studies of its most fundamental properties are only available by artificial production. At the radioactive ion beam facility ISOLDE at CERN, 208Po was produced by proton-induced spallation of uranium. Using the technique of in-source Resonance Ionization Spectroscopy the ionization threshold was probed with a tunable dye laser. A spectrum of 110 previously undocumented odd-parity Rydberg states was observed. Applying the Rydberg formalism to the data enabled the determination of the first ionization energy of polonium as 67896.310(14)(30)cm−1 or 8.4180700(18)(37) eV. This is a precision improvement of more than 600 over the existing literature value. A comparison with the homologous elements sulfur, selenium and tellurium enabled the assignment of the electron configuration of the resonances found in the spectrum.